LOW-TEMPERATURE MAGNETIC HYSTERESIS PROPERTIES OF PARTIALLY OXIDIZED MAGNETITE - Kosterov A. (My University, 2002)
Hysteresis loops have been measured as a function of temperature between 10 K and room temperature for two samples of pseudo-single-domain magnetite. One sample, with mean grain size of 2-3 μm, displays just surface oxidation, the bulk of the material remaining relatively stoichiometric with a Verwey transition temperature (T V ) of 112 K. In contrast, another sample, which contains much finer grains (~0.15 μm), having been exposed to air for about 20 yr, shows evidence of oxidation affecting the whole grain volume. This process has apparently formed two-phase grains in which the core is composed of non-stoichiometric magnetite with a T V of 95 K, and a superficial layer of probably pure maghemite. In accordance with previous studies, for both samples hysteresis properties below the Verwey transition depend critically on the mode of cooling through the transition. The difference in sample stoichiometry affects the temperature dependence of the hysteresis properties over the whole temperature range studied. Below the Verwey transition, the (relatively) stoichiometric sample shows a behaviour fairly close to that reported previously for a sample of similarly sized magnetite with a T V of 118 K. Common features include a rapid decrease of theM rs /M s ratio with increasing temperature after cooling in a strong magnetic field (FC), compared with the near constancy of this parameter after zero-field cooling (ZFC); (2) equally rapid decrease of the coercive force with increasing temperature after ZFC; (3) a small but significant difference between the temperature dependences of the coercive force after ZFC for a demagnetized versus a magnetized starting magnetic state. In the non-stoichiometric sample some of these features are also observed; however, it also shows a distinctive behaviour of the M rs /M s ratio after ZFC, which reaches a maximum at 30-35 K. Above the Verwey transition, the stoichiometric sample shows the behaviour typical of magnetite, i.e. an increase in the M rs /M s ratio and the coercive force, which starts approximately 10 K above the T V and extends up to 200-210 K. In contrast, in the non-stoichiometric sample both parameters just slowly decrease between 110 K and room temperature.
Keywords: MAGNETIC DOMAINS; MAGNETITE; PHASE TRANSITIONS